Testing the Waters: How Firms Enter New Markets - Carsten Eckel; Ina Charlotte Jäkel; Luca Macedoni; Raymond Riezman (CESifo GmbH, 2024)
Using firm-level data on production and trade from Denmark, we document that firms frequently employ a strategy of entering new export markets with Carry-Along Trade (CAT), i.e., with products manufactured by other firms. This strategy is surprising because, empirically, CAT products have below average market shares and mark-ups, and trade models predict firms to focus on core products with large sales in export markets with additional fixed and variable costs. To rationalize this new stylized fact, we propose a model where CAT plays a pivotal role in enabling firms to learn about market conditions and assess market viability. In our framework, exporting own-produced core products requires upfront sunk entry investments that create a benefit of knowing the exact market conditions. Firms can learn these market conditions by either investing first based on expected market conditions, or by exporting CAT products that do not require additional investments. We provide empirical evidence in support of our mechanism by showing that entering with CAT is particularly prevalent (i) among small firms, (ii) in distant markets, and (iii) among firms with no prior exporting experience.
Keywords: F14; F12; 330; market entry; carry-along trade; delivery of own goods; learning